Pengaruh Penilaian Prestasi Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Fakultas Ekonomi Dan Bisnis USU - Sorta Ida Sianipar; Dahrul Siregar; Teddi Pribadi; wan Rizca Amelia (Universitas Medan Area, 2022)
The purpose of this study is to determine how the influence of job performance appraisal and career development on employee performance at the USU Faculty of Economics and Business. The type of research used is associative research, where the variables are measured using the Likert scale method. Data collection in this study was conducted by interview, questionnaires, and direct documentation surveys. The population in this study was 44 people, then the sample was taken using the saturated sampling method, which took the entire population as a sample. Data processing was carried out using the SPSS application, the data analysis method used was descriptive analysis and inferential statistical analysis using multiple linear regression analysis. The results of this study indicate that simultaneously, there is a significant effect of job performance assessment and career development on employee performance at the USU Faculty of Economics and Business. Then, partially assessing work performance and career development each has a positive and significant effect on employee performance at the USU Faculty of Economics and Business.